Satu Kajian Terhadap Tahap Kemahiran Kakitangan Sokongan I Kumpulan C yang Menjalankan Tugas Kewangan atau Perakaunan di Jabatan Akauntan Negara, Malaysia, Cawangan Selangor D. E. - Rahmad Julkifli, Mohd. Ali (2004)
This study was conducted to determine the skill level of the Supporting Staff I Group C in performing their financial or accounting duties. The staff in this case are those whose job titles either Administrative Assistant (Financial) Grade W17, Accounts Assistant Grade W17, Administrative Assistant (Financial) Grade W22 and Accounts Assistant Grade W22. Analysis was done to determine whether the skill levels of the independent variables namely financial and accounts skill, computer skill, work skill and interpersonal relationship skill are related to the skill level of the dependent variable which is the skill required in performing financial or accounting duties. The data was obtained through self-administrative questionnaire. The target population covered all of the Supporting Staff I Group C whom are responsible to the financial or accounting duties in Accountant General Department, Selangor D.E. branch. This study indicated that the skill levels of financial and accounts, computer, work and interpersonal relationship are related to the level of the skill required in performing financial or accounting duties. The study also showed the need to increase the skill levels of both computer and financial and accounts. It is hoped that the proposals of this study will help the management of the Accountant General Department, Selangor D.E. branch to find ways of solving the weaknesses of their staff in performing financial or accounting duties. These weaknesses had been queried repetitively by the Auditor General Department.